Gingerol extract-stabilized silver nanoparticles and their applications: colorimetric and machine learning-based sensing of Hg(ii) and antibacterial properties - Kittiya Plaeyao; Ratchaneekorn Kampangta; Yuparat Korkokklang; Chanon Talodthaisong; Apichart Saenchoopa; Saengrawee Thammawithan; Krailikhit Latpala; Rina Patramanon; Navaphun Kayunkid; Sirinan Kulchat (My University, 2023)
This study focused on synthesizing ginger-stabilized silver nanoparticles (Gin-AgNPs) using a more eco-friendly method that utilized AgNO3 and natural ginger solution. These nanoparticles underwent a color change from yellow to colorless when exposed to Hg2+, enabling the detection of Hg2+ in tap water. The colorimetric sensor had good sensitivity, with a limit of detection (LOD) of 1.46 μM and a limit of quantitation (LOQ) of 3.04 μM. Importantly, the sensor operated accurately without being affected by various other metal ions. To enhance its performance, a machine learning approach was employed and achieved accuracy ranging from 0% to 14.66% when trained with images of Gin-AgNP solutions containing different Hg2+ concentrations. Furthermore, the Gin-AgNPs and Gin-AgNPs hydrogels exhibited antibacterial effects against both Gram-negative and Gram-positive bacteria, indicating potential future applications in the detection of Hg2+ and in wound healing.
Keywords: Silver nanoparticle; Tap water; Nanoparticles: synthesis and applications